2007
DOI: 10.1677/joe-07-0144
|View full text |Cite
|
Sign up to set email alerts
|

Differential androgen and estrogen substrates specificity in the mouse and primates type 12 17β-hydroxysteroid dehydrogenase

Abstract: Recently, we have shown that human and monkey type 12 17b-hydroxysteroid dehydrogenases (17b-HSD12) are estrogen-specific enzymes catalyzing the transformation of estrone (E 1 ) into estradiol (E 2 ). To further characterize this novel steroidogenic enzyme in an animal model, we have isolated a cDNA fragment encoding mouse 17b-HSD12 and characterized its enzymatic activity. Using human embryonic kidney cells (HEK)-293 cells stably expressing mouse 17b-HSD12, we found that in contrast with the human and monkey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 43 publications
(37 reference statements)
3
31
0
Order By: Relevance
“…On the other hand, in the presence of the cDNA insert encoding let-767, high conversion of 4-androstenedione into testosterone and estrone into estradiol has been observed, thus indicating that LET-767 is able to convert androgen as well as estrogen substrates. The situation is similar to that observed with the mouse 17b-HSD12 (Blanchard & Luu-The 2007) that possesses a small size amino acid (L) at position 234. In human, 17b-HSD12 (Luu-The et al 2006) has lost the ability to metabolize androgen that is produced by the isoform 17b-HSD3 (Geissler et al 1994).…”
Section: Effect Of Rna Interference (Rnai) Of Let-767 Expression On Tsupporting
confidence: 81%
See 3 more Smart Citations
“…On the other hand, in the presence of the cDNA insert encoding let-767, high conversion of 4-androstenedione into testosterone and estrone into estradiol has been observed, thus indicating that LET-767 is able to convert androgen as well as estrogen substrates. The situation is similar to that observed with the mouse 17b-HSD12 (Blanchard & Luu-The 2007) that possesses a small size amino acid (L) at position 234. In human, 17b-HSD12 (Luu-The et al 2006) has lost the ability to metabolize androgen that is produced by the isoform 17b-HSD3 (Geissler et al 1994).…”
Section: Effect Of Rna Interference (Rnai) Of Let-767 Expression On Tsupporting
confidence: 81%
“…However, in contrast with the human enzymes that show substrate specificity, LET-767 catalyzes the transformation of 4-androstenedione into testosterone as well as estrone into estradiol, similar to that found in the mouse 17b-HSD12 (Blanchard & Luu-The 2007). Previously, we have shown that the amino acid F234 is responsible, in part, for the androgenic-estrogenic substrate specificity.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In humans, the highest expression of HSD17B12 is detected in the tissues involved in lipid metabolism, including the liver, kidney and muscle (Sakurai et al 2006). In mice, the expression has also been detected in the brown and white adipose tissue (Moon & Horton 2003, Sakurai et al 2006, Blanchard & Luu-The 2007. Studies on zebra fish have, furthermore, supported the role of HSD17B12 in fatty acid synthesis (Mindnich et al 2004), and studies with LET-767, the Caenorhabditis elegans ortholog of HSD17B12, have shown that the enzyme is required for the production of branched-chain and longchain fatty acids in vivo (Entchev et al 2008).…”
Section: Hsd17b12mentioning
confidence: 99%